Postural deformities: potential morbidities to cause balance problems in patients with ankylosing spondylitis? - Çınar, Ece; Akkoç, Yeşim; Karapolat, Hale; Durusoy, Raika; Keser, Gökhan (European journal of rheumatology, 2016)
Abstract Objective: This study aimed to assess the impact of postural deformities caused by ankylosing spondylitis (AS) on balance problems.   Material and Methods: This study included 29 patients with AS and 21 healthy controls. For assessing exercise capacity and dynamic balance, timed up and go test, five times sit-to-stand test, gait speed, and 6-min walk test were performed. Romberg tests were used to evaluate static balance and proprioception, whereas Dynamic Gait Index (DGI), Functional Gait Assessment (FGA), Berg Balance Scale (BBS), Activity Specific Balance Confidence Scale (ABC), Dizziness Handicap Inventory (DHI), and functional reach test were used to assess dynamic balance and the risk of falling. Using Bath Ankylosing Spondylitis Metrology Index (BASMI) scores, patients with AS were divided into two groups: those with scores 0–4 were assigned to subgroup AS1, and those with scores 5–10 were assigned to subgroup AS2.   Results: In the whole group of patients with AS, five times sit-to-stand test, tandem Romberg test with eyes closed, and BBS and ABC scores were significantly worse than the healthy controls (p<0.05). In the AS2 subgroup having more severe and advanced disease, five additional parameters, including timed up and go test, 6-min walk test, functional reach test, FGA, and DHI scores were also significantly worse than the healthy controls (p<0.05). Comparing the two subgroups with each other, only BBS scores were significantly worse in the AS2 subgroup than in the AS1 subgroup.   Conclusion: Although in clinical practice, poor balance is not a common problem in AS, possibly because of compensatory mechanisms, patients with AS have poorer static and dynamic balance than healthy subjects. Significantly worse BBS scores in the AS2 subgroup than in the AS1 subgroup may suggest the presence of more dynamic balance problems in advanced disease; however, future studies comprising larger samples are necessary to confirm this assumption.